(untitled) (Bangladesh Journal of Botany, 2008)
The influence of four levels of fertilizers viz. 0:0:0, 60:65:80, 120:130:160 and 240:260:320 kg/ha (N:P:K) on growth, yield and yield contributing characters of six onion genotypes viz. Thaherpuri Brown, BARI Onion 1, Faridpuri Bhati, Suksagar, Nasirbala and Pusa Red exhibited distinct variation in respect of all the characters under investigation in the field condition. The fertilizers at 120:130:160 kg/ha produced the maximum bulb yield (14.9 t/ha). Genotype Pusa Red gave the maximum bulb yield (17.2 t/ha) and Faridpuri Bhati had the lowest yield (11.8 t/ha). Pusa Red along with 120:130:160 kg/ha produced maximum bulb yield (18.3 t/ha). Correlation studies revealed that bulb yield was positively related with different yield components, but it showed non-significant negative relation with bulb dry matter content (%). The regression analyses showed that the rate of change of bulb yield was dependent upon the rate of change of plant height, number of leaves and roots, and root length. Increase in number of roots per plant appears very important in increasing the yield. Â Key words: Allium cepa, Onion, Fertilizer, Genotypes, Correlation, Regression doi:10.3329/bjb.v36i1.1546 Â Bangladesh J. Bot. 36(1): 33-38, 2007 (June)